If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z = 5xy + -3 Reorder the terms: z = -3 + 5xy Solving z = -3 + 5xy Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Simplifying z = -3 + 5xy
| g(x)=4f(x)-1 | | 2=15*x | | 12a+3+2a-1= | | 750-50x=-185-35x | | 2-(2*y)=y+64 | | 7x^2-4+x=15x | | 2=110*x | | y-5=y-9 | | 6x^2-4x+0=0 | | 53-x+8=4x-27+1 | | (2w+3)2+2x=42 | | 3(7-2k)=57 | | -8+4m^2-5m^2= | | 7x+3-2x+9=47 | | z-8.4=4 | | (x+(2+i))(x+(2-i))=0 | | -0.2(212-h)=8.6 | | 5x-10=39 | | 5.25b=22.75 | | -5x-2=-x-7 | | 3(x+1)+3(x+3)= | | 14x-(4x-5)=45 | | 7x-26=2x+54 | | -7(5k-5)=-210 | | 25-3u=24 | | 95=5X+2X+7 | | 2=10-1.6d | | 95=5X+2X+7 | | 95=5X+2X+6 | | 95=5X+2X+6 | | 5x-3(x-5)=-8+4x+17 | | 95=5X+2X+6 |